Transformasi Pembelajaran Kewirausahaan melalui Modul Digital Interaktif Menggunakan Learning Management System berbasis Moodle di SMK Muhammadiyah 6 Rogojampi - Ratri, Indira Nuansa; Prasetyo, Junaedi Adi; Suardinata, I Wayan; Kurniawan, Bagus; Putra, Naufal Herdhana (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
SMK Muhammadiyah 6 Rogojampi is a private vocational school in Banyuwangi committed to developing students’ scientific competence and Islamic values through skill-based learning. However, the learning process is still dominated by conventional methods such as lectures and manual assignments, which are less relevant to the demands of the digital era. This condition has resulted in low digital literacy among students and the absence of an integrated learning platform that supports interactive and adaptive learning. This community service activity aims to transform entrepreneurship learning through the development of an interactive digital module using a Moodle-based Learning Management System (LMS) at SMK Muhammadiyah 6 Rogojampi. The implementation method includes needs analysis, digital module design and development, training for teachers and students on the use of LMS, and pilot implementation in entrepreneurship classes. The results show that both teachers and students were able to operate the LMS effectively, and the developed interactive digital module enhanced learning participation and students’ understanding of entrepreneurial concepts. In addition, students were able to practice creating business plans digitally through the interactive features available on the Moodle platform. This activity concludes that integrating a Moodle-based LMS with interactive digital modules can serve as an effective solution to improve the quality of entrepreneurship learning in vocational schools. Future activities are recommended to expand the implementation of this approach to other subjects to strengthen digital literacy and prepare students for technology-based industries.